“MY FIRST SEXUAL KNOWLEDGE” VIDEO-ANIMATION-BASED FOR THE PROTECTION OF CHILDREN AGED 4-6 YEARS FROM SEXUAL VIOLENCE - Zuhriyah, Siti; Ndari, Susianty Selaras (Journal of Early Childhood Education (JECE), 2021)
The purpose of this research is to develop media “my first sexual knowledge